Respiratory Failure in a Pediatric Patient with Biventricular Assist Devices: Identification and Novel Management of Inflow Cannula Obstruction. Issue 4 (July 2015) - Stidham, Timothy R.; Auerbach, Scott R.; Mitchell, Max B.; Buckvold, Shannon M.
Abstract : Respiratory failure after ventricular assist device (VAD) placement may threaten transplant candidacy and can be lethal. Refractory respiratory failure may require addition of extracorporeal membrane oxygenation (ECMO) support. Providing ECMO in a VAD-supported patient is uniquely challenging, particularly in the case of LVAD inflow cannula obstruction in a pediatric patient who may be more prone to cannula obstruction. Surgical intervention to alleviate obstruction may not be feasible. Here, we present a novel nonsurgical strategy for conversion to ECMO in a VAD-supported pediatric patient with respiratory failure because of LVAD inflow cannula obstruction.